2012
DOI: 10.1007/s00701-012-1446-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of intraventricular central neurocytoma: 92 cases

Abstract: Central neurocytomas mostly occur in the lateral ventricle system near the foramen of Monro. Therefore, total resection is the best treatment. Two surgical approaches are possible as treatment. Calcifications or adhesions affect the gross total resection of the tumour. Radiation therapy or radiosurgery therapy can be chosen as a salvage treatment in case of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 57 publications
1
39
2
1
Order By: Relevance
“…It occurs rarely in people younger than 20 years or older than 40 years of age. Most studies have reported that the patients seem to be equally prevalent in either sex (9,16,19,26). In our series, there was no significant sex variation with the male/female ratio being 1:1.1, and the patients ranged from 14 to 59 years of age (mean, 26.3 years).…”
Section: Epidemiologymentioning
confidence: 64%
See 3 more Smart Citations
“…It occurs rarely in people younger than 20 years or older than 40 years of age. Most studies have reported that the patients seem to be equally prevalent in either sex (9,16,19,26). In our series, there was no significant sex variation with the male/female ratio being 1:1.1, and the patients ranged from 14 to 59 years of age (mean, 26.3 years).…”
Section: Epidemiologymentioning
confidence: 64%
“…As CNs have a deep-seated intraventricular location, an abundant blood supply, and proximity to critical structures such as the fornix and thalamus, the surgical morbidity and mortality rates were relative high (6,8,(10)(11)(12)(13)(14)19,23). some reported rates of GTR ranged from 31% to 88%, mortality rates varied between 0% and 19%, and morbidity rates varied between 16% and 52% (Table IV).…”
Section: Surgical Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of the small ventricle, tumors involving both the frontal horn and midline are best removed by an interhemispheric-transcallosal approach. Some reports further stated that if the ventricular border is close to the surface, such as less than 2 cm or close to the very most lateral border, a transcortical approach should be chosen (8). Decreased incidences of seizure, porencephalic cyst formation, and subdural hygroma were reported to be advantages of interhemispheric-transcallosal approaches (3,4,16).…”
Section: Discussionmentioning
confidence: 99%